2021
DOI: 10.1542/peds.2020-028357
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropulmonary Blastoma in Pediatric Lung Lesions

Abstract: BACKGROUND: Pediatric lung lesions are a group of mostly benign pulmonary anomalies with a broad spectrum of clinical disease and histopathology. Our objective was to evaluate the characteristics of children undergoing resection of a primary lung lesion and to identify preoperative risk factors for malignancy. METHODS: A retrospective cohort study was conducted by using an operative database of 521 primary lung lesions manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
2
15
0
2
Order By: Relevance
“…Study radiologists increased the sensitivity for detecting a malignant primary lesion to 58% but had reduced specificity (83%) when compared with the original CT interpretation (eTable 2 in Supplement 1 ). Based on the estimated disease prevalence of PPB among postnatally diagnosed lung lesions, 16 the calculated PPV was 24% and the NPV was 95%. The sensitivity of the study radiologists for detecting a CPAM was 56% and the specificity was 70%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study radiologists increased the sensitivity for detecting a malignant primary lesion to 58% but had reduced specificity (83%) when compared with the original CT interpretation (eTable 2 in Supplement 1 ). Based on the estimated disease prevalence of PPB among postnatally diagnosed lung lesions, 16 the calculated PPV was 24% and the NPV was 95%. The sensitivity of the study radiologists for detecting a CPAM was 56% and the specificity was 70%.…”
Section: Resultsmentioning
confidence: 99%
“… 21 , 38 , 39 Less than 5% of PPBs are detected prenatally. 18 , 20 , 40 , 41 The only radiologic feature that is thought to be pathognomic for benign disease is the presence of a systemic feeding vessel, 16 , 18 and our study radiologists correctly excluded malignancy in their review of all confirmed BPS lesions. The significance of other image-based characteristics in identifying PPB is more controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many patients with PPB were found to have a negative family history for PPB-associated cancer. 13 Therefore, screening for DICER1 carriers among her siblings or first-degree relatives may be beneficial, as it can potentially lead to the earlier detection of related cancers or type 1 PBB before progression to types 2 and 3.…”
Section: Discussionmentioning
confidence: 99%